Watershed Sustainability and Composite Index: Application and Challenges - Branchi, Bruna Angela (Sociedade & Natureza, 2022)
The need for efficient water resources management highlights the importance of discussing the watershed sustainability issue. This is a complex subject, which justifies the choice for multidimensional indexes. The aim of this paper is to discuss the assessment of watersheds’ sustainability through composite indices to detect this statistical instrument’s strengths and weaknesses. This is a descriptive, exploratory, and quantitative research. The literature review on sustainability indices and their application in hydrographic basins guided the selection of a watershed sustainability index (WSI). The dual approach that combines the criteria of the Pressure-State-Response (PER) model with the dimensions of the Hydrology-Environment-Life-Policy model (UNESCO HELP model) guided the selection of the fifteen indicators that were chosen. The WSI was used to assess the degree of sustainability of the Piracicaba, Capivari and Jundiaí river basins during two periods in the 2010s. The analysis of the results detected a minor decrease in the index’s value, due to the Hydrology and Politics dimensions that recorded a setback in the second half of the decade under analysis. The result was not worse because of the remarkable improvement recorded in the Life dimension. This compensation is a weakness of the WSI that implicitly promotes the concept of weak sustainability. On the other hand, the selection of indicators guided by the dual approach is particularly interesting and challenging by connecting the PER criteria with the dimensions of sustainability well summarized in the HELP model.